Gestión financiera y su impacto en la rentabilidad de la microempresa skynet del cantón Quevedo, año 2012. - Cifuentes Giler, Olga Estefanía (2015)
Skynet is a small business located in the canton Quevedo, on October 7th Avenue, between Sixth and Seventh streets, Local No. 609, began operations in 2009 as a result of effort, perseverance and entrepreneurial vision of its owner, in the field of development of technological products, especially mobile communication equipment. According to 73.96% of the population surveyed in Quevedo, determined to be excellent service and care provided by the micro Skynet also has improved over time. The 73.96% of respondents said they are satisfied by the services received by the micro. Of the services provided, which has caused greater impression on the population, related to the care in selling cell with 33.33%, followed by care by purchasing airtime.